Comparison of three different biomaterials used in in vitro molar apexification models - Elif Ece Kalaoglu; Canan Duman; Belen Sirinoglu Capan; Mert Ocak; Burak Bilecenoglu (BMC, 2023)
Abstract Objectives New biomaterials had some advantages such as mixing and easier application as compared to traditional MTA in single step apexification method. This study aimed to compare the three biomaterials used in the apexification treatment of immature molar teeth in terms of the time spent, the quality of the canal filling and the number of x-rays taken to complete the process. Methods The root canals of the extracted thirty molar teeth were shaped with rotary tools. To obtain the apexification model, ProTaper F3 was used retrograde. The teeth were randomly assigned into three groups based on the material used to seal the apex; Group 1: Pro Root MTA, Group 2: MTA Flow, Group 3: Biodentine. The amounts of the filling, the number of radiographs taken until treatment completion and the treatment duration were recorded. Then teeth were fixed for micro computed tomography imaging for quality evaluation of canal filling. Results Biodentine was superior to the other filling materials according to time. MTA Flow provided greater filling volume than the other filling materials in the rank comparison for the mesiobuccal canals. MTA Flow had greater filling volume than ProRoot MTA in the palatinal/distal canals(p = 0.039). Biodentine had greater filling volume more than MTA Flow in the mesiolingual/distobuccal canals (p = 0.049). Conclusions MTA Flow was found as a suitable biomaterial according to the treatment time and quality of root canal fillings.